A Multi-Criteria Decision-Making Approach for EvaluatingBusiness Excellence ‎Frameworks for The Indian Automotive Sector: A Qualitative Assessment - J, Eugene; R. , Dr. Arivazhagan (International Journal of Accounting and Economics Studies, 2025)
The Indian automotive component sector is undergoing rapid transformation. It is driven by ‎intensified global competition, stringent OEM expectations, and the accelerated adoption of ‎Industry 4.0 technologies. Classical Business Excellence Frameworks (BEFs)—such as ‎EFQM, the Malcolm Baldrige National Quality Award (MBNQA), and the Deming Prize—‎have traditionally supported excellence initiatives; however, their suitability within today’s ‎digitally evolving and culturally complex Indian manufacturing context remains unclear. Based ‎on these gaps, an Extended Business Excellence Framework (EBEF) was developed, ‎integrating digital transformation, information standardization, sustainability, and enhanced ‎PDCA cycles. This study evaluates these various BEFs using qualitative practitioner insights ‎and structured Multi-Criteria Decision-Making (MCDM) methods. Semi-structured interviews ‎with 15 senior automotive leaders identified six major evaluation criteria: ease of ‎implementation, cultural adaptability, effectiveness, efficiency, speed and cost . Using real-‎number TOPSIS and COPRAS analyses, the EBEF consistently outperformed classical BEFs, ‎with sensitivity and volatility analysis confirming its robustness. The findings offer a ‎contemporary, industry-aligned excellence model capable of supporting Indian automotive ‎suppliers in transitioning to Quality 4.0 environments‎.